BUDDHIST LOVING-KINDNESS AND COMPASSIONIN VIETNAMESE RAP MUSIC – THE CASE OF DEN VAU - Thuy Chung, Truong; Diep Anh, Nguyen (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
Since its introduction to Vietnam, Buddhism has been deeply intertwined with local culture and influenced many aspects of Vietnamese spiritual life, including contemporary art such as rap music. However, to date, there have been few academic studies that provide important insights into contemporary Vietnamese rap as well as the influence of Buddhism on rap. This study examined the rap lyrics of Den Vau, one of the particularly famous rap artists in contemporary Vietnamese music. Seven rap songs were chosen alongside a descriptive, thematic analysis was conducted. Through qualitative content analysis, this study explores how Buddhist concepts of loving-kindness and compassion are embedded in Den Vau’s rap lyrics. The analysis reveals two main themes: (1) loving-kindness, demonstrated through human relationships (including equal love for all people and filial piety to parents) and environmental consciousness; and (2) compassion, manifested in empathy for various groups (youth, parents, children, all beings) as well as self-compassion. While previous studies often associated rap music with harmful influences, this research indicates how rap can serve as a platform for conveying positive Buddhist values. By examining Den Vau’s rap lyrics, the study illuminates the unique fusion of Buddhist philosophy with contemporary rap artistry in the Vietnamese context, highlighting how global art forms can effectively transmit local values and positive messages.